2019
DOI: 10.1038/s41598-019-54721-x
|View full text |Cite
|
Sign up to set email alerts
|

Female bias in an immigratory population of Cnaphalocrocis medinalis moths based on field surveys and laboratory tests

Abstract: Sex ratio bias is common in migratory animals and can affect population structure and reproductive strategies, thereby altering population development. However, little is known about the underlying mechanisms that lead to sex ratio bias in migratory insect populations. In this study, we used Cnaphalocrocis medinalis, a typical migratory pest of rice, to explore this phenomenon. A total of 1,170 moths were collected from searchlight traps during immigration periods in 2015–2018. Females were much more abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Females that emerge early are more likely to disperse because they need to find food and locate suitable oviposition sites. Similar to our results, earlier female emergence has been reported in migratory insects such as Pseudaletia unipuncta (Haworth) (Lepidoptera: Noctuidae) [ 33 ], Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) [ 34 ] and Cnaphalocrocis medinalis (Guenée) (Lepidoptera: Pyralidae) [ 35 ]. Furthermore, migratory female insects possess a greater migration capacity than males, which ensures the rapid expansion of migratory populations.…”
Section: Discussionsupporting
confidence: 90%
“…Females that emerge early are more likely to disperse because they need to find food and locate suitable oviposition sites. Similar to our results, earlier female emergence has been reported in migratory insects such as Pseudaletia unipuncta (Haworth) (Lepidoptera: Noctuidae) [ 33 ], Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) [ 34 ] and Cnaphalocrocis medinalis (Guenée) (Lepidoptera: Pyralidae) [ 35 ]. Furthermore, migratory female insects possess a greater migration capacity than males, which ensures the rapid expansion of migratory populations.…”
Section: Discussionsupporting
confidence: 90%
“…Useful RCS and CLPP information may also be obtainable via electromagnetic modelling [42], though with reduced strength of inference if used for target identification. Knowledge of the temperature-range for sustained flight for each species of interest will also have interpretive value and may be obtained through careful laboratory measurement [43] or inferred from field observations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, female moths have stronger flight propensity than males in some species [64], which undertake the task of finding food and oviposition sites [65]. Guo et al [36] reported that female C. medinalis had a greater migratory propensity and flight capability than males at constant 26 °C in a laboratory population. Similar patterns were observed in M. separata [66] and Culex pipiens pallens [67].…”
Section: Discussionmentioning
confidence: 99%
“…The lower value of the period of eclosion represented the synchronized eclosion. The sex ratio was used to calculate the proportion of female and male adults [36].…”
Section: Larval Development Of C Medinalismentioning
confidence: 99%
See 1 more Smart Citation